PENGARUH FLASH SALE DAN GRATIS ONGKIR TERHADAP KEPUTUSAN PEMBELIAN E-COMMERCE MAHASISWA SUKABUMI - Agustian, Sultan; Adistria, Fisxi; Al Giffari, M.Raffli (REUGREUG: Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2026)
This study aims to empirically test and analyze the influence of flash sales and free shipping on e-commerce purchase decisions among students in the Sukabumi region. Using a causal quantitative approach, the study involved 100 respondents selected through non-probability sampling with a purposive sampling method. Data were collected using a structured questionnaire and analyzed through a Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS) with the assistance of SmartPLS 3 software. The results show that the flash sale variable has a positive and significant effect on purchase decisions with a t-statistic value of 4.557 and a p-value of 0.000. Likewise, the free shipping variable also demonstrates a positive and significant effect with a t-statistic value of 6.132. The R-Square value of 0.958 indicates that these two promotional strategies simultaneously explain 95.8% of the variance in consumer purchase decisions. These findings confirm that promotional strategies based on time urgency and free shipping incentives are highly effective in encouraging digital shopping behavior among students, with free shipping found to have a relatively stronger influence than flash sales.